2017
DOI: 10.5114/biolsport.2017.64585
|View full text |Cite
|
Sign up to set email alerts
|

Association of arch height with ankle muscle strength and physical performance in adult men

Abstract: Differences in arch height may have a certain impact on lower extremity muscle strength and physical performance. However, there is little evidence from investigation of the possible correlation of arch height with ankle muscle strength and physical performance measures. Sixty-seven participants took part in this study. Arch height index (AHI) was assessed and categorized using a 3-dimension foot scanner. Ankle muscle strength was measured employing a dynamometer. Physical performance measures including agilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
1
18
0
5
Order By: Relevance
“…According to the current study, the apparent importance of anthropometric variables in running speed may have biomechanical implications. Although researchers have explored the general association between foot structure and ankle muscle strength [ 30 ], few studies have investigated foot and ankle structure and their correlation with functional abilities in sprinting. A recent study indicated the influence of the foot proportions on running speed [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the current study, the apparent importance of anthropometric variables in running speed may have biomechanical implications. Although researchers have explored the general association between foot structure and ankle muscle strength [ 30 ], few studies have investigated foot and ankle structure and their correlation with functional abilities in sprinting. A recent study indicated the influence of the foot proportions on running speed [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, few studies have focused on investigating the relationships between foot morphology and ankle muscle strength. Zhao et al [28] collected foot morphology and ankle muscle strength through a foot scanner and dynamometer, respectively, and found that foot length and foot width are positively correlated with ankle joint muscle strength. Our study showed that foot length, foot width, and truncated foot length were correlated with toe flexor strength through similar methods of foot morphology measurements.…”
Section: Relationships Between Foot Morphology and Foot Muscle Strengthmentioning
confidence: 99%
“…Maka dari itu, orang dengan kondisi flat foot mengeluhkan adanya ketidaknyamanan atau rasa sakit yang tidak normal pada kakinya serta adanya gejala klinis seperti ketidakstabilan pergelangan kaki, plantar fasciitis, dan achilles tendinitis, sedangkan adanya tekanan yang terus menerus pada sisi luar atau sisi lateral pada cavus foot dapat menyebabkan terjadinya plantar callus serta lebih banyak mengalami stress fracture. 12,22,25 Pentingnya bagi orang tua untuk mengetahui tipe kaki pada anak, khususnya pada tipe kaki flat foot dan cavus foot karena memiliki insiden stress fractures yang lebih besar dibandingkan dengan tipe arkus normal pada anak yang sama-sama memiliki aktivitas tinggi.…”
Section: Diskusi Karakteristik Respondenunclassified